2007
DOI: 10.1002/art.22312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protease‐activated receptor 2 in murine models of arthritis

Abstract: ObjectiveProtease‐activated receptor 2 (PAR‐2) activation has been linked to pro‐ and antiinflammatory cellular responses. We undertook this study to explore the importance of PAR‐2 activation in 4 murine models of arthritis and to analyze the expression of PAR‐2 in human arthritic synovium.MethodsZymosan‐induced arthritis (ZIA), K/BxN serum–induced arthritis, and Freund's complete adjuvant (CFA)–induced arthritis were generated in naive PAR‐2−/− mice and PAR‐2+/+ littermates. Antigen‐induced arthritis (AIA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 15 publications
4
65
1
Order By: Relevance
“…Of the 4 PARs, the one most strongly implicated in the pathogenesis and progression of inflammatory arthritis is PAR-2 (41,42). Importantly, PAR-2 is also increased in OA human cartilage, can be up-regulated by IL-1␣ and TNF␣, and its activation leads to increased MMP-1 and MMP-13 synthesis (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 4 PARs, the one most strongly implicated in the pathogenesis and progression of inflammatory arthritis is PAR-2 (41,42). Importantly, PAR-2 is also increased in OA human cartilage, can be up-regulated by IL-1␣ and TNF␣, and its activation leads to increased MMP-1 and MMP-13 synthesis (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…K14 activates PAR-1, −2, and −4, and K5 and K6 activate PAR-2 [196]. Notably, PAR-2-deficient mice are protected from CFA-induced arthritis [32] and are more resistant to EAE [191].…”
Section: Direct Modulation Of Immune Effectormentioning
confidence: 99%
“…17). Synovial fibroblasts, chondrocytes, macrophages, neutrophils, mast cells, T cells, and dendritic cells all express PARs, which exhibit both antiinflammatory and proinflammatory properties, although recent data point toward a detrimental role especially in the context of immune-mediated effects in arthritis (157). A study in PAR-2 Ϫ/Ϫ mice confirmed PAR-2 as a key mediator of chronic joint inflammation (158), and this is likely to be a consequence of activation by mast cell-derived tryptase (86,87).…”
Section: Serine Proteinases and Cell Signalingmentioning
confidence: 99%